(untitled) (Revista de História da UEG (REVHIST), 2019)
Abstract: Studies focused on the history of Brazilian radio consider that the radio was a daily companion of the population for all hours in countless situations. The different uses of this vehicle of communication generated from projects of national integration to new types of contacts with tastes, practices and customs from abroad. In this article, we intend to take part of this history of radio through the tracks left by the northern Goiás region of yore, state of Tocantins now. In this sense, we also reflect on the theoretical and methodological procedures around the challenges of narrating and constructing a radio history, given the difficulties, limitations and scarcity of sources inherent to such experience. The proposal aims to weave reflections about the radio as an instrument of, in and for society, with language and aesthetics inserted in a historical context favorable to the use of the North. The north of Goiás then, often presented as a place of backwardness, appears in this plot, from the radio, in another type of relationship based, above all, in line with other so-called modern spaces. Keywords: Radio. North of Goiás. Press. Tocantins History.